If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8.9y + -7.35 = 12.4y Reorder the terms: -7.35 + 8.9y = 12.4y Solving -7.35 + 8.9y = 12.4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12.4y' to each side of the equation. -7.35 + 8.9y + -12.4y = 12.4y + -12.4y Combine like terms: 8.9y + -12.4y = -3.5y -7.35 + -3.5y = 12.4y + -12.4y Combine like terms: 12.4y + -12.4y = 0.0 -7.35 + -3.5y = 0.0 Add '7.35' to each side of the equation. -7.35 + 7.35 + -3.5y = 0.0 + 7.35 Combine like terms: -7.35 + 7.35 = 0.00 0.00 + -3.5y = 0.0 + 7.35 -3.5y = 0.0 + 7.35 Combine like terms: 0.0 + 7.35 = 7.35 -3.5y = 7.35 Divide each side by '-3.5'. y = -2.1 Simplifying y = -2.1
| 3-6x=-2x-37 | | 6+.10x=0.15x+8 | | -7x+7(-3x+18)=-14 | | 15h-11h=20 | | 1.25n=4 | | -5/6+x=11/6 | | -5=(x+9) | | 12x+14+10v=80 | | 36/x-8=6/7 | | 5x-9=-3x-25 | | x/5-13=22 | | y=7/8(0)+5y | | 6x+2(6x-3)=-144 | | 2x-2x/7=x/2+17/2 | | 16x+1=-14 | | 2(x+10)=x-7 | | -5(w+5)= | | -6x-76=98-12x | | -1+6x=3x-19 | | (27p^6)^(5/3) | | -6-k+2-5k= | | 8x-2(x-8)=6(x+1)+7 | | 5-10t=-25 | | 40=5x+2(-x+2) | | x^2-23x=3 | | -2y+9-y=-7y-7 | | y/6-4=6 | | z/5-6=2/1/6 | | -15h-8.8h-20=20-19.8h | | 12g-3g--9g=-18g | | 0=5x^2+4x-18 | | 3x-9=68-4x |